2023
DOI: 10.1002/ejhf.2856
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multimorbidity on mortality in heart failure with reduced ejection fraction: which comorbidities matter most? An analysis of PARADIGM‐HF and ATMOSPHERE

Abstract: Aims Multimorbidity, the coexistence of two or more chronic conditions, is synonymous with heart failure (HF). How risk related to comorbidities compares at individual and population levels is unknown. The aim of this study is to examine the risk related to comorbidities, alone and in combination, both at individual and population levels. Methods and results Using two clinical trials in HF – the Prospective comparison of ARNI (Angiotensin Receptor–Neprilysin Inhibitor) with ACEI (Angiotensin‐Converting Enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
4
3
1
Order By: Relevance
“…Our results are consistent with a recent pooled analysis of the PARADIGM‐HF and the ATMOSPHERE trials including 15 066 patients and showing that >93% of HFrEF patients had at least one comorbidity and 79% had at least two comorbidities 7 . In our study we found that about 98% of HF patients had at least one comorbidity (94% had at least one CV comorbidity and 85% had at least one non‐CV comorbidity).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with a recent pooled analysis of the PARADIGM‐HF and the ATMOSPHERE trials including 15 066 patients and showing that >93% of HFrEF patients had at least one comorbidity and 79% had at least two comorbidities 7 . In our study we found that about 98% of HF patients had at least one comorbidity (94% had at least one CV comorbidity and 85% had at least one non‐CV comorbidity).…”
Section: Discussionsupporting
confidence: 93%
“…The most common comorbidities were hypertension (65%), atrial fibrillation (56%) and CAD (52%), followed by CKD (40%) and anaemia (34%). Results are consistent with those in the PARADIGM‐HF and ATMOSPHERE trials 7 . On the other hand, we found a significantly higher prevalence of atrial fibrillation (ranging from 51% to 66% in patients with HFrEF and HFpEF, respectively) compared to the previously motioned analyses from trials (24–36%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with the findings of other studies, CV comorbidities such as hypertension, atrial fibrillation, coronary artery disease were more prevalent in HF patients 8 while mental and behavioural diseases such as depression and dementia were less prevalent across the HF spectrum studied. Obesity was associated with reduced mortality but increased hospitalizations across the HF spectrum.…”
supporting
confidence: 91%